Efficacy of Chinese herbal medicine on nasal itching in children with allergic rhinitis: a systematic review and meta-analysis - Chen, Yuhang; Wang, Jie; Wu, Liqun; Zhang, Ye; Chen, Hong; Zhang, Ziwei (Frontiers in Pharmacology, 2023)
Background: Allergic rhinitis is prevalent among children and can cause nasal itching, fatigue, and even hinder growth and development. The main discomfort symptom of allergic rhinitis is nasal itching. Clinical reports suggest that Chinese herbal medicine (CHM) is effective in allergy rhinitis treatment. Therefore, we evaluate the clinical efficacy of Chinese herbal medicine in treating nasal itching caused by allergic rhinitis in children. Methods: Nine databases, including PubMed, Embase, The Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wan Fang Data, CQVIP, Chinese Biological Medicine, and ClinicalTrials.gov, were systematically searched from their inception until March 2023. Randomized controlled trials (RCTs) comparing the efficacy of Chinese herbal medicine, either alone or in combination with Western medicine, to Western medicine treatment or placebo intervention for treating allergic rhinitis in children were eligible for inclusion. The effectiveness of Chinese herbal medicines for nasal itching was mainly evaluated. The Risk of Bias tool 2.0 assessed the risk of bias. Statistical analysis using RevMan 5.3 and Stata/SE 12. The quality of evidence was evaluated by GRADEpro 3.6. Risk ratios (RR) with corresponding 95% confidence intervals (CI) were utilized to evaluate and present dichotomous data, while mean difference (MD) and standardized mean difference (SMD) were employed for continuous data. A fixed-effects model was applied in cases where the data exhibited homogeneity (p > 0.1, I2 < 50%), whereas a random-effects model was utilized for heterogeneous data. Statistical significance was determined by a p-value <0.05. This study was conducted by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and its review protocol was registered on the International Platform for Registered Systematic Reviews and Meta-Analysis Programs (INPLASY202340076). Results: The review incorporated 23 studies. The meta-analysis indicated that herbal medicine was significantly related to the reduction of nasal itching (MD = −0.59, 95%CI: −0.94–0.24) and the increase of interleukin 10 level (SMD = 1.47, 95% CI: 0.90–2.05). Compared to Western medicine, the combining herbs and Western medicine showed better efficacy in relieving nasal itching, inhibiting immunoglobulin E, interleukin 4 and 33, enhancing interleukin 10, improving therapeutic efficiency, and reducing recurrent. Oral herbal medicine was more effective in treating nasal itching (MD = −0.45, 95% CI: −0.62–0.29). Combining oral and external herbal medicines was more efficient in treating nasal itching (MD = −0.44, 95% CI: −0.54–0.33), inhibiting immunoglobulin E, interleukin 4 (SMD = −0.87, 95% CI: −1.24–0.50) and 33 (SMD = −1.16, 95% CI: −1.54–0.77), and improving therapeutic efficiency. External herbal medicine did not show differences compared to Western medicines. Regarding safety, herbal medicine alone exhibited fewer adverse events than Western medicine; combining herbal and Western medicine showed no significant variation in adverse event incidence. Conclusion: Chinese herbal medicine (CHM) holds great potential in alleviating symptoms, modulating immune factors levels, and reducing relapse in pediatric rhinitis. Meanwhile, CHM is relatively safe. However, the efficacy and safety of CHM in treating pediatric rhinitis still need to be confirmed due to the inclusion of studies with low methodological quality, small sample sizes, and potential heterogeneity. More high-quality research is necessary to provide reliable evidence for the clinical application of CHM. Systematic Review Registration: INPLASY.com, identifier INPLASY202340076